The Influence of “Guru Penggerak” Competency and the Utilization of Learning Resources on the Quality of Education in Elementary Schools - Artadhewi Adhi Wijaya; Yovitha Yuliejantiningsih; Titik Haryati (Lembaran Ilmu Kependidikan, 2025)
Background - This study was motivated by the poor quality of education in elementary schools in Randublatung Subdistrict and the suspected influence of the suboptimal competence of “Guru Penggerak” and the suboptimal utilization of learning resources. Purpose - The objectives of this study were to determine: (1) the influence of “Guru Penggerak” competency on the quality of education in elementary schools in Randublatung District, (2) the influence of learning resource utilization on the quality of education in elementary schools in Randublatung District, and (3) the simultaneous influence of “Guru Penggerak” competency and learning resource utilization on the quality of education in elementary schools in Randublatung District. Method/approach - This study used a quantitative approach with an ex-post facto research design. The research population consisted of all teachers in 30 elementary schools where “Guru Penggerak” were assigned in Randublatung District, Blora Regency, with a sample of 176 peer teachers of “Guru Penggerak”. Data collection techniques used questionnaires that had been tested for validity and reliability. Data analysis used correlation tests, simple regression, multiple regression, and determination tests. Findings - The results of the study indicate that: (1) there is a significant influence of the competence of the “Guru Penggerak” on the quality of education in Randublatung Subdistrict, amounting to 82.3%, with the highest contribution from the personal competence dimension (80.6%) and the lowest from the professional competence dimension (28%), with the highest dimension of educational quality being the process dimension at 0.933 and the lowest being the input dimension at 0.930; (2) there is a significant influence of learning resource utilization on educational quality at 85.5%, with the highest contribution from the learning resource selection dimension (83.6%) and the lowest from the learning resource development dimension (62.8%); (3) there is a simultaneous influence of Guru Penggerak competencies and learning resource utilization on education quality of 91.4%. Conclusions - This study also provides empirical evidence of a significant influence of the competence of the “Guru Penggerak” and learning resource utilization on educational quality in elementary schools. Novelty/Originality/Value - The novelty of this study lies in its focus on the competence of “Guru Penggerak as other researchers have studied only the value and role of “Guru Penggerak”.